If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = 2x + 7x + 3 Multiply f * x fx = 2x + 7x + 3 Reorder the terms: fx = 3 + 2x + 7x Combine like terms: 2x + 7x = 9x fx = 3 + 9x Solving fx = 3 + 9x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = 3x-1 + 9 Simplifying f = 3x-1 + 9 Reorder the terms: f = 9 + 3x-1
| -7(x+5)-15=11+2 | | x^2-2x-1=16 | | 3x^2+6-45=0 | | -3x-9x=48 | | -3x-9x=49 | | t^2-6t+3=0 | | 5x+4y=68 | | 256a^4+81b^4= | | (5x-9)-(x+1)=0 | | 4z=50.8 | | 12k^2+4k=21-7k | | (z^2)-z+5=0 | | 9x+6y=4x-5y | | 56=1.4t | | 49y^2=36 | | 72+(X*.20)=70 | | 5x+2y-5z=40 | | 7log(9x-5)=1 | | 35.00+0.75x=50.00 | | 7x-27=8 | | 35.00+0.75=50.00 | | s^2-4s-3=0 | | x=1/2+2 | | x=1/2-2 | | 0=1/2-2y | | .1111x=2x-x^2 | | 5(-0.2)+1=x | | 9x-23=9x+-8 | | 6(5y+1)-5y=1 | | z^2-5z+3=0 | | 60x+40=700 | | 60+40=700 |